Lymphoepithelial carcinoma in parotid gland related to EBV infection: A case report. Issue 1 (February 2018) - Maeda, Hiroyuki; Yamashiro, Takuya; Yamashita, Yukashi; Hirakawa, Hitoshi; Agena, Shinya; Uehara, Takayuki; Matayoshi, Sen; Suzuki, Mikio
Abstract: Lymphoepithelial carcinoma commonly occurs at the nasopharynx and rarely occurs at other sites in the head and neck region. It is well known to occur at limited patients of local area as Asia or Arctic Circle. Related to this point, it is pointed out that this tumor has strong relation with Epstein–Barr Virus (EBV) infection. In this time, we experienced to treat lymphoepithelial carcinoma with metastatic cervical lymph nodes occurring at parotid gland. The morbidity ratio of this tumor is less than one percent of all parotid gland tumors. Moreover, we proved the infection of EBV to tumor cell by in situ hybridization (ISH). Incidentally, because it is considered that this tumor has well sensitivity against irradiation or anti-tumor drugs, prognosis of this tumor is better than that of other head and neck tumors with different pathological type. Actually, we tried to perform chemotherapy twice in (Nedaplatin (CDGP) 60 mg/m 2  × day 2 and 5-FU 600 mg/m 2  × day 5) and to irradiate about 70 Gy dose against parotid gland and cervical lymph nodes. It could not find local recurrence or metastasis as of now after five years from treatment.